Supplemental parenteral nutrition in cancer care: why, who, when. (September 2022) - Cotogni, Paolo; Bozzetti, Federico; Goldwasser, François; Jimenez-Fonseca, Paula; Roelsgaard Obling, Sine; Valle, Juan W.
Malnutrition is an often-overlooked challenge for patients with cancer. It is associated with muscle mass reduction, poor compliance and response to cancer treatments, decreased quality of life, and reduced survival time. The nutritional assessment and intervention should be a vital part of any comprehensive cancer treatment plan. However, data on artificial nutrition supplied based on caloric needs during cancer care are scarce. In this review, we discuss the recommendations of the European and American societies for clinical nutrition on the use of nutritional interventions in malnourished patients with cancer in the context of current clinical practice. In particular, when enteral nutrition (oral or tube feeding) is not feasible or fails to meet the complete nutritional needs, supplemental parenteral nutrition (SPN) can bridge the gap. We report the available evidence on SPN in cancer patients and identify the perceived barriers to the wider application of this intervention. Finally, we suggest a 'permissive' role of SPN in cancer care but highlight the need for rigorous clinical studies to further evaluate the use of SPN in different populations of cancer patients.